Advanced Adsorbent Mediated Extraction Techniques for the Separation of Antibiotics from Food, Biological, and Environmental Matrices. Issue 3 (3rd July 2022) - Sanyal, Doyeli; Mathur, Purvi
ABSTRACT: Estimation of antibiotic residues in environmental matrices; veterinary products; food and biological samples has become very important in order to protect the human health and limit the spread of antimicrobial resistance. To achieve this, sensitive and efficient sample preparation procedures for the extraction of antibiotics from complex matrices are essential. Reproducible and effective sample preparation processes together with sensitive analytical techniques directly impact the final accuracy of the data and further interpretation. Exhaustive solvent-based extraction techniques such as liquid–liquid extraction have several limitations and suffer from a negative impact on environment. Past two decades have witnessed paradigm shift from solvent based to sorbent-based techniques in the extraction of contaminants. Innovative non-exhaustive techniques such as solid-phase microextraction and magnetic solid-phase extraction using advanced (nano)materials (e.g. molecularly imprinted polymer) have brought radical changes to the way traditional sample extraction was carried out. As the advanced techniques are specific to a target antibiotic or to its class, design consideration for the in-house synthesis of novel (nano)materials and optimization of the extraction technique is a crucial step in the quantification of antibiotic contaminants. The aim of this review is to assess the critical design parameters to be considered to synthesize novel sorbent materials for the extraction of antibiotics and to improve their extraction techniques.